DISTINGUISHING OF THE SIGNALS IN NONLINEAR DETERMINISTIC TRACKING SYSTEMS - Шматок, С. О.; Петренко, А. Б.; Шматок, О. С. (Science-based technologies, 2016)
In this paper was investigated the signal capture mode on the automatic tracking. Was presented the technique of quantitative evaluation of signal resolution process in deterministic nonlinear tracking systems first and second orders based on bifurcation (accident) theory. The calculation of the parametric characteristics of the discriminator if there is any pair of input signals. Calculated the capture spot, determined equilibrium state and assessed the stability of the first and second order tracking system. Sizes of capture spot depend strongly on the radio signals capacity. Was constructed the phase portraits of nonlinear tracking system. Was determined the stalled conditions of tracking useful signal.